A Preliminary Study on the Architectural Design of Chinese Hospitals in Virus Era. Issue 1 (June 2020) - Cui, Zhang
Abstract: After the new Corona Virus Disease 2019 (COVID-2019), we have many new ideas for architectural design, more emphasis on epidemic prevention issues, designers in the functional design to meet the needs of medical staff and patients to use the design of the hospital, The assembly of hospital buildings is not only a transformation of construction methods, but also an upgrade of design concepts, which is a direction for future hospital development.